Does an organic strategy pay? An explanatory study of the Italian wine industry. Issue 10 (7th October 2019) - Dainelli, Francesco; Daddi, Tiberio
Abstract : Purpose: The relationship between businesses, green strategies and financial performance has become the focus of interest for many academics, practitioners and policymakers in recent years, with often controversial results. Surprisingly, very few contributions have been made by the wine sector to this debate. The purpose of this paper is to investigate the financial advantages of Italian winemakers who opt for green strategies and obtain voluntary organic certification. Design/methodology/approach: The authors compared the financial performance of 76 organic and 76 non-organic winemaking companies by means of 20 fundamental indicators of growth, profitability and solvency. The data were collected through an analysis of the 2014–2016 official annual reports. The authors used the compound annual growth rate measures, focusing on the median due to its robust characteristics. The authors then used non-parametric tests to examine the differences between the two samples. Findings: The growth of organic companies was almost three times that of their rivals between 2014 and 2016. Both the premium price and lower costs lead to an increase in the gross margin. However, the huge investments required for organic production weigh heavily on the financial statements; although having financed these investments with a higher share of equity capital, the organic companies present a higher level of capitalisation. Originality/value: Wine is a part of an agricultural industry that is too often based on industrialised food production processes. This study demonstrates the need for greener strategies that can benefit the producers, consumers and the environment. This is the first cross-sectional analysis and peer review to focus on the wine industry.